FISH mapping in Xenopus pygmaeus refines understanding of genomic rearrangements and reveals jumping NORs in African clawed frogs - Bergelová, Barbora; Gvoždík, Václav; Knytl, Martin (Heredity, 2025)
Chromosomal rearrangements are fundamental evolutionary drivers leading to genomic diversification. African clawed frogs (genus Xenopus, subgenera Silurana and Xenopus) represent an allopolyploid model system with conserved chromosome numbers in species with the same ploidy within each subgenus. Two significant interchromosomal rearrangements have been identified: a translocation between chromosomes 9 and 2, found in subgenus Silurana, and a fusion between chromosomes 9 and 10, probably widespread in subgenus Xenopus. Here, we study the allotetraploid Xenopus pygmaeus (subgenus Xenopus) based on in-depth karyotype analysis using chromosome measurements and fluorescent in situ hybridization (FISH). We designed FISH probes for genes associated with translocation and fusion to test for the presence of the two main types of rearrangements. We also examined the locations of 5S and 28S ribosomal tandem repeats, with the former often associated with telomeric regions and the latter with nucleolus organizer regions (NORs). The translocation-associated gene mapping did not detect the translocation in X. pygmaeus, supporting the hypothesis that the translocation is restricted to Silurana, but instead identified a pericentromeric inversion on chromosome 2S. The fusion-associated gene mapping confirmed the fusion of chromosomes 9 and 10, supporting this fusion as an ancestral state in subgenus Xenopus. As expected, the 5S repeats were found predominantly in telomere regions on almost all chromosomes. The nucleolar 28S repeats were localized on chromosome 6S, a position previously found only in the closely related species X. parafraseri, whereas other, phylogenetically more distant species have NORs located on different chromosomes. We therefore hypothesize that a jumping mechanism could explain the relatively frequent changes in the location of NORs during Xenopus evolution.
Keywords: Xenopus; Chromosome Mapping; karyotypizace; hybridizace in situ fluorescenční; genová přestavba; Karyotyping; karyotyp; molekulární evoluce; translokace genetická; Nucleolus Organizer Region; Evolution, Molecular; genom; Animals; Gene Rearrangement; mapování chromozomů; organizátor jadérka; zvířata; Translocation, Genetic; In Situ Hybridization, Fluorescence; Genome; Karyotype